Medical and Social Countermeasures for Tokyo Olympic in 2021 - Miyata, Y.; Hasegawa, N.; Nagase, H.; Kutsumura, N.; Nagatomi, R.; Nakamura, K.; Majima, T. (The Journal of Physical Fitness and Sports Medicine, 2020)
Throughout the past Sports events, we have discussed the Tokyo Olympics and the epidemic of infectious diseases. The Tokyo Olympics have been postponed due to COVID19 infection, in different situation but by infectious diseases. The situation and the Tokyo Olympics itself may be canceled if adequate countermeasures are not taken against infectious diseases. [Purpose] To identify the effective countermeasures against infectious to hold the Tokyo Olympic Games in 2021. [Method] In addition to conducting a risk assessment of the new covid19 known to date, enumerating the possible measures against it, countermeasures at waterside, protection of athletes, protection of spectators, possible risks after the Olympics and countermeasures. [Results] Examination of the world outbreak situation revealed that the conventional strengthening of public health alone was not sufficient to suppress the new covid19. In addition, it became clear that border protection could not work either. [Discussion / Conclusion] As for virus infection removalmethod, it has already been experienced that relying on alcohol is not sufficient, and the importance of zone defense by spatial virus infection removal method has been clarified. We must also consider the active use of medicines. At the same time, measures against drug resistance (AMR), which have been assumed so far, should be promoted.